2010
DOI: 10.1177/1043986209359369
|View full text |Cite
|
Sign up to set email alerts
|

A General Strain Theory of Prison Violence and Misconduct: An Integrated Model of Inmate Behavior

Abstract: Explanations of prison violence and other forms of misconduct have been dominated by three competing models: (a) the deprivation model, (b) the importation model, and (c) the coping model. We propose that these three seemingly competing models can be integrated within Agnew's general strain theory (GST). GST enriches the deprivation model by revealing three distinctive categories of strain. GST encompasses the importation model in hypothesizing that criminal cultural values and affiliations will structure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 82 publications
2
159
0
13
Order By: Relevance
“…Victimization experiences in particular are connected with PTSD (Kilpatrick et al, 2003), although few studies have considered PTSD in a GST framework. PTSD may increase the likelihood of criminal coping, especially among populations at risk for continued victimization (Blevins, Listwan, Cullen, & Jonson, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Victimization experiences in particular are connected with PTSD (Kilpatrick et al, 2003), although few studies have considered PTSD in a GST framework. PTSD may increase the likelihood of criminal coping, especially among populations at risk for continued victimization (Blevins, Listwan, Cullen, & Jonson, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…La aplicación de las EA en ambientes penitenciarios se realiza sobre la base de considerar, al menos, la prisión como un suceso traumático para una persona (S. D. Phillips, 2010;Rodríguez Díaz, Álvarez Fresno, García Zapico, Longoria, & Noriega Carro, 2013;Rodríguez Díaz et al, 2011), que impacta y genera una cadena de estresores -difi cultades de pareja, disminución de ingresos, comunicación con los seres queridos (hijos, padres, pareja, …), alejamiento familiar, drogodependencia, … (Degobbi & Rezende, 2011;Mikulic & Crespi, 2004;Moreno & Mellizo, 2006), así como límites para manejar difi cultades y generar cambios en la conducta (French & Gendreau, 2006) y pensamientos (Giordano, Cernkovick, & Rudolph, 2002), así como para mantenerlas estables a lo largo de la intervención con el interno para adaptarse a diferentes contextos (Blevins, Johnson, Cullen, & Lero, 2010;Johnson, Colvin, Hanley, & Flannery, 2010), dando lugar a nuevas pautas comportamentales, de roles y modalidades relacionales como forma de adaptarse a sus demandas y requerimientos (Pereira, Scheffer, & Martins de Almeida, 2012;Rodríguez Díaz, Álvarez Fresno, García Zapico, Longoria, & Noriega Carro, en prensa). Es decir, las EA son básicas a la hora de lograr construir una nueva historia de vida para el individuo que necesita de una nueva oportunidad, si cabe todavía más para aquellos que se refi eren en el ámbito de la inadaptación social.…”
Section: Y Agencia Española De Cooperaciónunclassified
“…While some research shows that increasing the prison population reduces crime through incapacitation [116,178], 22 other research indicates that the effect is modest [212], that this inverse relationship between crime and imprisonment diminishes as imprisonment rates increase [117], 23 and that the crime-reducing benefits of incapacitation may be offset by the crime-promoting effects associated with a high number of ex-prisoners in the community [62]. 24 Accordingly, additional crime committed by EM monitorees (compared to incapacitated inmates) is likely to be more than offset by reductions in post-release crime of prisoners if EM proves to be a more effective rehabilitator, and avoids the other social costs associated with high rates of imprisonment that may contribute to crime. For example, a study of offenders placed on home confinement in Florida found that there was an almost 95% reduction in the likelihood of revocation for a new offence for offenders subject to EM compared to those not [138].…”
Section: (A) Incapacitationmentioning
confidence: 99%
“…23 In fact, the effect may even become positive with high imprisonment rates [117]. 24 While selectively incapacitating high-risk offenders is likely to be more successful in reducing crime, in practice this can be difficult to implement due to challenges in accurately predicting the likelihood of reoffending [146]. It also raises concerns over differential treatment of offenders [157], and the associated increase in prison costs may exceed any benefit of reduced crime [25].…”
Section: (A) Incapacitationmentioning
confidence: 99%
See 1 more Smart Citation